Malignant stroke in a ticagrelor non-responder as a complication following aneurysm treatment with the Pipeline Embolization Device™. Issue 3 (June 2017) - Ghamasaee, Pegah; Carr, Kevin; Johnson, Jeremiah; Grandhi, Ramesh
The Pipeline Embolization Device™ (PED; Covidien Neurovascular Inc, Irvine, CA, USA) is a flow-diverting stent often used for the endovascular treatment of large or giant, wide-necked intracranial aneurysms of the internal carotid artery. Because of the inherent thrombogenicity of intracranial stents, dual-antiplatelet therapy is initiated after placement, which has been shown to decrease morbidity and mortality related to perioperative ischemic events in neurointerventional procedures. However, in some series, as much as 50% of patients demonstrate clopidogrel non-responsiveness. In these non-responders, alternate agents such as ticagrelor can be used to achieve adequate anticoagulation. Compared with clopidogrel, a prodrug requiring Cytochrome P450 enzymolysis for activation, ticagrelor directly and reversibly inhibits the P2Y12 ADP receptor. The absorption of the prodrug and the formation of its active metabolite is comparatively quicker ( t max 1.3–2 hours; 1.5–3 hours, respectively). To date, there have been no documented cases of ticagrelor non-responsiveness involving patients undergoing placement of flow-diverting stents or other endovascular neuro-interventional procedures.